Role of sex and sex hormones in PD-L1 expression in NSCLC: clinical and therapeutic implications - Rodriguez-Lara, Vianey; Soca-Chafre, Giovanny; Avila-Costa, Maria Rosa; Whaley, Juan Jose Juarez-Vignon; Rodriguez-Cid, Jeronimo Rafael; Ordoñez-Librado, José Luis; Rodriguez-Maldonado, Emma; Heredia-Jara, Nallely A. (Frontiers in Oncology, 2023)
Currently, immunotherapy based on PD-1/PD-L1 pathway blockade has improved survival of nonsmall cell lung cancer (NSCLC) patients. However, differential responses have been observed by sex, where men appear to respond better than women. Additionally, adverse effects of immunotherapy are mainly observed in women. Studies in some types of hormone-dependent cancer have revealed a role of sex hormones in anti-tumor response, tumor microenvironment and immune evasion. Estrogens mainly promote immune tolerance regulating T-cell function and modifying tumor microenvironment, while androgens attenuate anti-tumor immune responses. The precise mechanism by which sex and sex hormones may modulate immune response to tumor, modify PD-L1 expression in cancer cells and promote immune escape in NSCLC is still unclear, but current data show how sexual differences affect immune therapy response and prognosis. This review provides update information regarding anti-PD-1/PD-L immunotherapeutic efficacy in NSCLC by sex, analyzing potential roles for sex hormones on PD-L1 expression, and discussing a plausible of sex and sex hormones as predictive response factors to immunotherapy.